Photon Upconverting Nanophosphors: Unique Reporters for Optical Biosensing - Arppe, Riikka (fi=Turun yliopisto|en=University of Turku|, 2015)
Upconversion photoluminescence is a unique property of mostly certain inorganic materials, which are capable of converting low-energy infrared radiation into a higher-energy emission at visible wavelengths. This anti-Stokes shift enables luminescence detection without autofluorescence, which makes the upconverting materials a highly suitable reporter technology for optical biosensing applications. Furthermore, they exhibit long luminescence lifetime with narrow bandwidths also at the optical window of biomaterials enabling luminescence measurements in challenging sample matrices, such as whole blood. The aim of this thesis was to study the unique properties and the applicability of nano-sized upconverting phosphors (UCNPs) as reporters in biosensing applications. To render the inorganic nanophosphors water-dispersible and biocompatible, they were subjected to a series of surface modifications starting with silica-encapsulation and ending with a bioconjugation step with an analyte-recognizing biomolecule. The paramagnetism of the lanthanide dopants in the nanophosphors was exploited to develop a highly selective separation method for the UCNP-bioconjugates based on the magnetic selectivity of the high gradient magnetic separation (HGMS) system. The applicability of the nano-sized UCNPs as reporters in challenging sample matrices was demonstrated in two homogeneous sensing applications based on upconversion resonance energy transfer (UC-RET). A chemosensor for intracellular pH was developed exploiting UC-RET between the UCNP and a fluorogenic pH-sensitive dye with strongly increasing fluorescence intensity in decreasing pH. The pH-independent emission of the UCNPs at 550 nm was used for referencing. The applicability of the pH-nanosensor for intracellular pH measurement was tested in HeLa cells, and the acidic pH of endosomes could be detected with a confocal fluorescence microscope. Furthermore, a competitive UC-RET-based assay for red blood cell folic acid was developed for the measurement of folate directly from a whole blood sample. The optically transparent window of biomaterials was used in both the excitation and the measurement of the UC-RET sensitized emission of a near-infrared acceptor dye to minimize sample absorption, and the anti-Stokes detection completely eliminated the Stokes-shifted autofluorescence. The upconversion photoluminescence efficiency is known to be dependent on crystallite size, because the increasing surface-to-volume ratio of nano-sized UCNPs renders them more susceptible to quenching effects of the environment than their bulk counterpart. Water is known to efficiently quench the luminescence of lanthanide dopants. In this thesis, the quenching mechanism of water was studied using luminescence decay measurements. Water was found to quench the luminescence of UCNPs by increasing the non-radiative relaxation of the excited state of Yb3+ sensitizer ion, which had a very strong quenching effect on upconversion luminescence intensity.

Käänteisviritteinen fotoluminesenssi on lähinnä tiettyjen epäorgaanisten nanomateriaalien ainutlaatuinen ominaisuus, jossa matalaenergistä infrapunasäteilyä muutetaan korkeampienergiseksi näkyvän aallonpituuden emissioksi. Tämä Stokesin siirtymän vastainen fotoluminesenssi mahdollistaa mittaamisen ilman autofluoresenssia, minkä takia käänteisviritetyt materiaalit soveltuvat leimoiksi optisiin biosensorisovelluksiin. Lisäksi ne tuottavat pitkäikäistä emissiota kapeilla kaistanleveyksillä myös aallonpituusalueilla, jotka biomateriaaleissa ovat optisesti läpinäkyviä, ja mahdollistavat näin luminesenssimittaukset myös hankalista näytemateriaaleista, kuten kokoverestä. Väitöskirjan tarkoituksena oli tutkia nanokokoisten käänteisviritteisten partikkelien ainutlaatuisia ominaisuuksia ja niiden käyttöä leimoina biosensorisovelluksissa. Nanopartikkelit pinnoitettiin silikalla ja analyyttejä tunnistavilla biomolekyyleillä. Partikkelien sisältämien lantanidi-ionien paramagneettisuutta käytettiin hyväksi kehitettäessä erittäin selektiivistä erotusmenetelmää biomolekyylipinnoitettujen partikkeleiden puhdistusta varten. Menetelmä perustui korkean gradientin magneettiseen erotteluun. Nanopartikkeleiden käyttöä leimoina hankalissa näytemateriaaleissa tutkittiin kehittämällä kaksi käänteisviritteisen luminesenssin resonanssienergiansiirtoon perustuvaa, erotusvapaata sovellusta. Väitöskirjassa kehitettiin kemiallinen sensori solunsisäisen pH:n tutkimiseen. Sensori perustui resonanssienergiansiirtoon nanopartikkelin ja pH-herkän pienmolekyylivärin välillä. pH-nanosensorin soveltuvuutta solunsisäisen pH:n mittaamiseen tutkittiin HeLa-soluilla, joiden endosomien hapan pH pystyttiin havaitsemaan fluoresenssimikroskoopin avulla. Väitöskirjassa kehitettiin myös kilpaileva pesuvaiheeton määritys, jolla punasolujen foolihappopitoisuus voidaan mitata suoraan kokoverinäytteestä. Biologisten materiaalien optisesti läpinäkyviä valon aallonpituuksia käytettiin sekä käänteisviritteisten nanopartikkelien virittämiseen että resonanssienergiansiirron vastaanottajapienvärin emission mittaamiseen, jotta pystyttiin minimoimaan kokoverinäytteen valon absorptio. Lisäksi Stokesin siirtymän vastainen fotoluminesenssi mahdollisti mittaamisen ilman autofluoresenssia. Käänteisviritteisen fotoluminesenssin tehokkuuden tiedetään olevan kidekokoriippuvainen, koska nanokokoisten partikkeleiden suuri pinnan ja tilavuuden välinen suhde altistaa partikkelit ympäristön luminesenssia sammuttaville vaikutuksille. Vesi sammuttaa tehokkaasti lantanidien luminesenssia, ja väitöskirjassa tutkittiin sen mekanismia tarkemmin luminesenssin elinikämittausten avulla. Veden havaittiin sammuttavan voimakkaasti käänteisviritteisten nanopartikkeleiden luminesenssia lisäämällä Yb3+ herkistimen virittyneen tilan säteilemätöntä purkautumista